Native Bottle Store Stands. 1961/10/26. Opposite East Gate of Dube House NAD/61/312; Stand no.1382, Naledi. NAD/61/322; Stand no 5, Mapetla.NAD/61/323; Stand no 9166, 9182, 9183, 9184. NAD/61/325 - City Engineers Department, Johannesburg. (My University, 2012)
SOWETO. Native Bottle Store Stands. 1961/10/26. Opposite East Gate of Dube House NAD/61/312; Stand no.1382, Naledi. NAD/61/322; Stand no 5, Mapetla.NAD/61/323; Stand no 9166, 9182, 9183, 9184. NAD/61/325
Native Bottle Store Stands. 1961/10/26. Opposite East Gate of Dube House NAD/61/312; Stand no.1382, Naledi. NAD/61/322; Stand no 5, Mapetla.NAD/61/323; Stand no 9166, 9182, 9183, 9184. NAD/61/325. 500X730 each.
Keywords: SOWETO. Native Bottle Store Stands. 1961/10/26. Opposite East Gate of Dube House NAD/61/312; Stand no.1382, Naledi. NAD/61/322; Stand no 5, Mapetla.NAD/61/323; Stand no 9166, 9182, 9183, 9184. NAD/61/325